2021
DOI: 10.1021/acsapm.0c00982
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Advanced Polymer Materials in Agriculture Related Applications

Abstract: Over the past few decades, advanced polymeric materials have gained popularity in the development of sustainable agricultural applications. Smart polymeric systems have extensively contributed to the agricultural industry by increasing the efficiency of pesticides, herbicides, and fertilizers by facilitating controlled release systems and, therefore, enabling lower doses to be used. Superabsorbent polymeric materials have been used as soil conditioners to control the impact of drought, whereas polycationic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 109 publications
0
81
0
1
Order By: Relevance
“…Recently, utilization of hydrogels in nutrient delivery in agricultural science and long-term drug delivery exhibits a significant interest [ 43 ]. Most of these methods require aqueous formulations to be delivered over a certain amount of time, yet a hydrophobicity for a long-term open-air application must be possessed in order to prevent the drying and a loss of a part [ 44 ]. Hydrophobic hydrogel is a novel concept that administers the surface properties of the initial network.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, utilization of hydrogels in nutrient delivery in agricultural science and long-term drug delivery exhibits a significant interest [ 43 ]. Most of these methods require aqueous formulations to be delivered over a certain amount of time, yet a hydrophobicity for a long-term open-air application must be possessed in order to prevent the drying and a loss of a part [ 44 ]. Hydrophobic hydrogel is a novel concept that administers the surface properties of the initial network.…”
Section: Resultsmentioning
confidence: 99%
“…Sustainable arable agriculture must provide sufficient nutrition for the growing global population. 40 To date, it has generally managed to increase productivity in line with growing need. As with other parts of the biosphere, the quality of available land is decreasing due to climate change, pollution and over-fertilisation leading to low nutrient use efficiency, and so we need to ensure that we understand, as far as is possible, new and increasing threats to crop production.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Oksińska et al [ 47 ] identified two bacteria, Rhizobium radiobacter 28SG and Bacillus aryabhattai 31SG, isolated from the watered SAP, that were able to biodegrade up to 36% of the similar copolymer of acrylamide and potassium acrylate containing 5.28% of unpolymerized monomers in 30 days. Despite the expected biodegradability, there are efforts to replace synthetic SAPs with natural ones such as starch [ 21 ], cellulose [ 14 ], chitosan or alginate [ 22 ], or with synthetic-biopolymer hybrid SAPs that combine the desired chemical properties of synthetic polymers–such as mechanical strength, high water capacity, and stability, and lower cost and biological safety of natural polymers [ 48 ]. Proteins are also currently gaining a lot of attention as a replacement for synthetic SAPs because they are biodegradable and available from agricultural waste [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%